Empathy Map Gen Z Towards Healthy Food: A Foodpreneur Design Strategy - Ulita, Novena; Kartanegara, Ath Thariq; Salsabila, Jihan; Saleh, Arifin; Queen, Zabenaso (Aptisi Transactions On Technopreneurship (ATT), 2024)
Healthy eating behavior is becoming increasingly prevalent in Indonesia, especially after the COVID-19 outbreak from 2020-2022, which highlighted the importance of diet for immunity. Generation Z, being a significant part of the Indonesian population, presents an opportunity for targeted public health promotions. This study aims to explore Generation Z attitudes towards healthy food to develop an effective Foodpreneur design strategy. Using a qualitative approach, data were collected through interviews and literature studies involving 29 Gen Z participants from various campuses. The research applied the design thinking method and the empathy map to derive a comprehensive strategy. The results revealed that while Gen Z acknowledges the importance of healthy eating for a balanced lifestyle, they face barriers such as economic constraints, taste preferences, and accessibility. However, there is a clear enthusiasm for promoting local and sustainable food practices. The findings suggest that an effective Foodpreneur design strategy should emphasize educating Gen Z on the benefits of local and healthy food, creating engaging and relatable promotional content, and leveraging social media to enhance awareness and accessibility. This approach can foster a culture of health consciousness and support local economies, aligning with Gen Z values and behaviors.